Effect of Ba impregnation on Al2O3 catalyst for 1-octene production by 1-octanol dehydration. (1st December 2020) - Kim, Young-eun; Jung, Unho; Song, Dahye; Im, Hyo Been; Park, Ji Chan; Hye Youn, Min; Jeong, Heon-Do; Rhim, Geun Bae; Chun, Dong Hyun; Lee, Dong-Wook; Lee, Ki Bong; Koo, Kee Young
Graphical abstract: Highlights: Ba impregnation enhanced the 1-octene selectivity by reducing the isomer formation. Ba promotion is favorable to 1-octene production through anti-Saytzeff elimination. 1.5 wt% Ba/Al2 O3 had the best reactant conversion, 1-octene selectivity and yield. 1-Octene selectivity decreased at higher Ba content (≥2.0 wt%) due to DOE formation. Abstract: This study investigated the effect of impregnating Ba into an Al2 O3 catalyst on the acid-base property and catalytic activity in the dehydration of 1-octanol to produce 1-octene. The Ba/Al2 O3 catalysts were prepared by the incipient wetness method with different Ba contents of 0.0–3.0 wt%, and characterized by ICP-MS, BET-BJH, XRD, pyridine-FTIR, and CO2 -TPD. The catalytic activity in 1-octanol dehydration was evaluated at 300, 350, and 400 °C with liquid hourly space velocity (LHSV) of 7–56 h −1 . As the amount of Ba increased, the density of the basic site on Ba/Al2 O3 increased, and the strength distribution of the Lewis acid site (LAS) was changed. Under the reaction condition of 400 °C and LHSV = 7 h −1, Ba/Al2 O3 showed higher 1-octene selectivity and 1-octene purity compared with the pure Al2 O3 even though the 1-octanol conversion was similar. This is because the added Ba eliminated the strong LAS, which, in turn, inhibited the side-reaction originating from the re-adsorption of 1-octene. When LHSV > 21 h −1, Ba/Al2 O3 catalysts showed decreased 1-octanol conversion but maintained high 1-octene selectivity and 1-octene purity. As the Ba content reached 2.0 wt%, 1-octene selectivity was decreased as the formation of dioctyl ether became more active than olefin production. Therefore, 1.5 wt% Ba/Al2 O3 is the optimal catalyst for producing 1-octene from 1-octanol in terms of 1-octanol conversion, 1-octene selectivity, and 1-octene yield.